DESAIN KOMUNIKASI VISUAL SEBAGAI SARANA PROMOSI PERGURUAN TINGGI - Dewi Immaniar; Reni Mulyani; Fitria Arnita (CCIT Journal, 2017)
Visual Communication Design as a Promotion Tool is a project that tries to describe a process of media design to inform a message regarding the promotion of an institution that is engaged in education that is STKIP Pasundan. Selection STKIP Pasundan is based on the consideration that this educational institution has great potential to compete with other similar educational institutions engaged in the field of College of Teacher Training and Education. Almost all educational institutions engaged in teacher training have the same facilities make the competition more difficult. Educational institutions that have long standing really have to be clever in attracting students to stay active and prospective students increase along with the many educational institutions that stand. Visual Communication Design is an appropriate means of promotion in building the identity of STKIP Pasundan to be able to compete and have a good image among the community. The basic design concept used is the simplicity / simplicity with the green color identity that is always applied in every design design. This concept is a simple concept that is able to attract attention. Seeing the conditions and problems, designed a visual communication design that can function effectively and variably that can convey information about STKIP Pasundan profile in detail and creative until the community and work relations image STKIP Pasundan Cimahi can be a positive recognition